A novel multifunctional FePt/BP nanoplatform for synergistic photothermal/photodynamic/chemodynamic cancer therapies and photothermally-enhanced immunotherapy. Issue 35 (7th August 2020) - Yao, Xiuxiu; Yang, Baochan; Wang, Shan; Dai, Zhichao; Zhang, Dongsheng; Zheng, Xiuwen; Liu, Qingyun
Abstract : A new multi-modal therapy agent FePt/BP–PEI–FA NCs, with FePt nanoparticles (FePt NPs) loaded onto ultrathin black phosphorus nanosheets (BPNs), has been constructed to enhance synergistic PTT, PDT and CDT that target primary tumors. Abstract : A new multi-modal therapy agent, FePt/BP–PEI–FA nanoplatform, with FePt nanoparticles (FePt NPs) loaded onto ultrathin black phosphorus nanosheets (BPNs), has been constructed to enhance synergistic photothermal therapy (PTT), photodynamic therapy (PDT), and chemodynamic therapy (CDT) that target primary tumors. In this work, BPNs exhibit excellent photothermal and photodynamic behaviors under different wavelength laser irradiation. After polyethylenimine (PEI) modification, FePt NPs with sizes of 3–4 nm are uniformly attached onto the surface of modified BPNs via electrostatic adsorption. FePt NPs, as a ferroptosis agent, can transform endogenous H2 O2 into reactive oxygen species (ROS) through the Fenton reaction, ultimately inducing cell death. Based on magnetic resonance imaging (MR) and thermal imaging, the as-prepared FePt/BP–PEI–FA NCs can inhibit tumor growth by achieving synergistic therapies. More significantly, combined with cytotoxic T lymphocyte-associated protein 4 (CTLA-4) checkpoint blockade, FePt/BP–PEI–FA NC-induced PTT can control both primary and untreated distant tumors' growth. Therefore, FePt/BP–PEI–FA NCs is a potential multifunctional nanoagent for effective anti-tumor applications.